1997
DOI: 10.1021/jp964096o
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Studies of the Reactions of Atomic Hydrogen with Iodoalkanes

Abstract: Rate constants for the reaction of H atoms with the alkyl iodides iodomethane (1), deuterated iodomethane (1d), iodoethane (2), 2-iodopropane (3), and 2-iodo-2-methyl propane (4) have been measured using the flash-photolysis resonance fluorescence technique. The results are k 1 ) (6.3 ( 0.6) × 10 -11 exp [((-5(T ) 295 K) and k 4 ) 2.0 × 10 -11 (T ) 294 K) cm 3 molecule -1 s -1 . The transition state for the substitution reaction H + CH 3 I f I + CH 4 was characterized at the Gaussian-2 level of ab initio theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 23 publications
3
14
1
Order By: Relevance
“…The uncertainty limits are indicated only in the temperature range of our measurements (950-1400 K). The numbered thin lines show previously published rate coefficients: (1) Kumaran et al [20] (p = 0.1-0.7 bar), (2) Yang and Conway [25] (p = 0.02 bar), (3) Shilov and Sabirova [26], (4) Ogg [27] (p = 0.2 bar), (5) Sullivan [17] (p = 0.2 bar), (6) Yang and Tranter [19] (p = 0.07-0.16 bar; plotted values are the high-pressure extrapolation), (7) Benson and Bose [28] (p = 0.08-0.25 bar), (8) Butler and Polanyi [29] (p = 0.002-0.017 bar), (9) Michael et al [11], (10) Vasileiadis and Benson [13], (11) Baulch et al [9], (12) Lorenz et al [16], (13) Sullivan [30], and (14) Yuan et al [21] Arrhenius parameters showed a significantly better agreement with the experimental results compared to the simulations performed with the initial parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The uncertainty limits are indicated only in the temperature range of our measurements (950-1400 K). The numbered thin lines show previously published rate coefficients: (1) Kumaran et al [20] (p = 0.1-0.7 bar), (2) Yang and Conway [25] (p = 0.02 bar), (3) Shilov and Sabirova [26], (4) Ogg [27] (p = 0.2 bar), (5) Sullivan [17] (p = 0.2 bar), (6) Yang and Tranter [19] (p = 0.07-0.16 bar; plotted values are the high-pressure extrapolation), (7) Benson and Bose [28] (p = 0.08-0.25 bar), (8) Butler and Polanyi [29] (p = 0.002-0.017 bar), (9) Michael et al [11], (10) Vasileiadis and Benson [13], (11) Baulch et al [9], (12) Lorenz et al [16], (13) Sullivan [30], and (14) Yuan et al [21] Arrhenius parameters showed a significantly better agreement with the experimental results compared to the simulations performed with the initial parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Note that these Arrhenius parameters were fitted to their experimental data, but this rate coefficient was influential only in the first 2 µs of their experimental curves (see the comment on p. 441 in ). Yuan et al also measured the rate coefficient of reaction (R5), but in a different temperature region (295–624 K). Westbrook and Dryer provided an estimation of the Arrhenius parameters of (R5), but it was not included in Fig.…”
Section: Mechanism Optimizationmentioning
confidence: 99%
“…Iodine atom abstraction reactions by H atoms are usually fast and the Kansas State Laboratory has successfully used the reaction of iodoalkanes with H atom as precursor for various radicals. [1][2][3][4] For example, the rate constants for the H þ CF 3 I=CH 3 I reactions [5][6][7] are both about 1 Â 10 À11 cm 3 molecule À1 s À1 . As the investigation proceeded, it was realized that the primary reaction, H þ CH 2 ClI, was interesting and needed to be characterized on its own merit.…”
Section: Introductionmentioning
confidence: 99%
“…Reactions of hydrogen atoms with alkyl iodides have been the subject of several kinetic studies [1][2][3][4][5][6][7], motivated in part by the potential contributions of iodine to combustion chemistry [8]. Interesting kinetics have been observed in some cases, such as Cl-atom addition [9] and O-atom addition followed by elimination of HOI [10].…”
Section: Introductionmentioning
confidence: 99%
“…Rather less attention has been paid to aryl iodides, which are of fundamental interest because they exhibit a range of mechanisms in radical reactions. For example, the reaction CH 3 + C 6 H 5 I appears to proceed via I-atom abstraction [11], as does I + C 6 H 5 I [12]. The Cl + C 6 H 5 I reaction was proposed to take place by an addition/I-atom elimination path [13], while OH + C 6 H 5 I appears to take place by addition below room temperature, and by H-atom abstraction at higher temperatures [14].…”
Section: Introductionmentioning
confidence: 99%